Intelligent Systems Technologies and Applications Volume 2 - Berretti, Stefano; Thampi, Sabu M.; Dasgupta, Soura; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book contains a selection of refereed and revised papers from three special tracks: Ad-hoc and Wireless Sensor Networks, Intelligent Distributed Computing and, Business Intelligence and Big Data Analytics originally presented at the International Symposium on Intelligent Systems Technologies and Applications (ISTA), August 10-13, 2015, Kochi, India.  .
Ad-hoc and Wireless Sensor Networks -- Intelligent Distributed Computing -- Business Intelligence and Big Data Analytics.
Keywords: Computational intelligence; Artificial intelligence; Computer networks .; Data mining; Computational Intelligence; Artificial Intelligence; Computer Communication Networks; Data Mining and Knowledge Discovery